METHOD FOR MANUFACTURING NITROGEN OXIDE ADSORBENT USING KMnO4

KR103018663B1Active Publication Date: 2026-09-16SUM CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020260042215
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2026-03-09
Publication Date
2026-09-16
Estimated Expiration
2046-03-09

Smart Images

  • Figure 112026028476627-PAT00001_ABST
    Figure 112026028476627-PAT00001_ABST
Patent Text Reader

Abstract

A method for manufacturing a nitrogen oxide adsorbent using KMnO4 according to one embodiment of the present invention comprises: (a) a step of forming a composite support by mixing a first support containing magnesium oxide (MgO) and a second support containing aluminum oxide (Al2O3) using a ball mill; (b) a step of preparing a precursor solution by dissolving potassium permanganate (KMnO4) in purified water; (c) a step of forming a sample by impregnating the composite support by dropping the precursor solution onto it; (d) a step of drying the sample; and (e) a step of finally drying the dried sample, wherein steps (c) and (d) may be repeated until the sample reaches a preset degree of impregnation. Through this, it is possible to have excellent nitrogen oxide adsorption performance compared to conventional commercially available adsorbents, while having low performance variation and excellent reproducibility, and furthermore, being suitable for mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing a nitrogen oxide adsorbent using KMnO4. Background Technology

[0002] Conventionally, adsorbents in which active components are supported on a porous carrier or adsorbents that combine oxidation and adsorption functions have been widely used to remove nitrogen oxides (NOx) from exhaust gases. In particular, since permanganate (KMnO4) possesses strong oxidizing power and can convert NO or NOx into forms such as nitrates, it is known to be utilized as an adsorbent for removing nitrogen oxides by being supported on a carrier such as alumina. However, these conventional KMnO4-based adsorbents are causing various problems under actual operating conditions.

[0003] First, conventional nitrogen oxide adsorbents have a problem in that active components are easily deactivated or adsorption performance rapidly deteriorates due to coexisting components such as moisture and sulfur oxides (SO2) contained in the exhaust gas. In particular, manganese-based or permanganate-based active components are prone to migration or leaching in the presence of moisture, and it has been pointed out that even if they initially exhibit a certain level of NOx removal performance, their performance becomes unstable or their lifespan is shortened during long-term operation. In addition, if the distribution of active components supported on the surface of the carrier or within the pores is not uniform, the active components may be excessively concentrated in specific areas or, conversely, areas lacking active sites may be formed, leading to a decrease in NOx adsorption efficiency and a problem of performance variation between batches.

[0004] Furthermore, conventional manufacturing methods utilizing impregnation or simple mixing processes have limitations due to low reproducibility depending on process conditions. Even when using the same composition, the physical properties of the final adsorbent can vary significantly depending on the degree of mixing, dispersion state, particle size distribution, and loading depth, which in turn leads to non-uniformity in nitrogen oxide adsorption performance. In particular, when repeated impregnation or high-concentration precursor solutions are used to increase the loading amount of active ingredients, problems such as reduced mechanical stability—including pore clogging, increased pressure loss, powder shedding, and wear—may occur, thereby imposing restrictions on actual device application.

[0005] In addition, in conventional nitrogen oxide adsorbent manufacturing technology, the influence of mechanical mixing conditions or the degree of energy input during the manufacturing process on the final adsorption performance was not sufficiently considered. In other words, the process design for precisely controlling the interaction between the active ingredient and the carrier, the formation of microstructures, and the dispersion state was insufficient, which limits the realization of adsorbents that maintain stable performance even under various operating conditions such as wet conditions, long-term operation, and repeated adsorption environments.

[0006] As such, conventional nitrogen oxide adsorbents face the problem that it is difficult to maintain stable performance under actual operating conditions due to not only limitations in the composition itself but also issues such as non-uniform dispersion of active components resulting from the manufacturing process, insufficient water resistance and durability, and reduced process reproducibility. Therefore, there is a need to develop a new manufacturing method that can precisely control the dispersion state of active components and their binding characteristics with the carrier, and stably achieve excellent nitrogen oxide adsorption performance even under various operating conditions. The problem to be solved

[0007] Based on the technical background described above, the present invention aims to provide a method for manufacturing a nitrogen oxide adsorbent using potassium permanganate (KMnO4) as an active ingredient, which has superior nitrogen oxide adsorption performance compared to conventional commercial adsorbents, while having low performance variation and excellent reproducibility, and furthermore is suitable for mass production. means of solving the problem

[0008] A method for manufacturing a nitrogen oxide adsorbent using KMnO4 according to one embodiment of the present invention comprises: (a) a step of forming a composite support by mixing a first support containing magnesium oxide (MgO) and a second support containing aluminum oxide (Al2O3) using a ball mill; (b) a step of preparing a precursor solution by dissolving potassium permanganate (KMnO4) in purified water; (c) a step of forming a sample by impregnating the composite support by dropping the precursor solution onto it; (d) a step of drying the sample; and (e) a step of finally drying the sample, wherein steps (c) and (d) may be repeated until the sample reaches a preset degree of impregnation.

[0009] Potassium permanganate (KMnO4) can be supported at a weight ratio of 1 to 20% relative to the composite support.

[0010] The ball mill can be operated for 1 to 5 hours at a rotational speed of 100 to 500 rpm. It can also be operated in a temperature range of 20 to 60 ℃. Effects of the invention

[0011] Through a method for manufacturing a nitrogen oxide adsorbent using KMnO4 according to one embodiment of the present invention, it is possible to manufacture a nitrogen oxide adsorbent that has superior nitrogen oxide adsorption performance compared to conventional commercial adsorbents, while having low performance variation and excellent reproducibility, and furthermore, is suitable for mass production. Brief explanation of the drawing

[0012] FIG. 1 is a flowchart of a method for manufacturing a nitrogen oxide adsorbent using KMnO4 according to one embodiment of the present invention. Figure 2(a) is a graph comparing the nitrogen oxide adsorption performance of adsorbents prepared according to different aluminum oxide particle sizes based on volume. Figure 2(b) is a graph comparing the nitrogen oxide adsorption performance of adsorbents prepared according to different aluminum oxide particle sizes on a weight basis. Figure 3 is a graph comparing the adsorption rate and trend of nitrogen oxides according to Figure 2. Figure 4 (a) is a graph comparing the nitrogen oxide adsorption performance according to the control of the ball mill's operating time. Figure 4(b) is a graph comparing the nitrogen oxide adsorption performance according to the rotation speed of the ball mill. Figure 5 is a graph comparing the nitrogen oxide adsorption performance of the ball mill according to Figure 4 at different reaction temperatures. Figure 6 (a) is a graph comparing the nitrogen oxide adsorption performance according to the presence or absence of moisture during the operation conditions of the ball mill. Figure 6 (b) is a graph comparing the nitrogen oxide adsorption performance according to the presence or absence of oxygen during the operation conditions of the ball mill. Figure 7 is a graph comparing the nitrogen oxide adsorption performance according to the potassium permanganate content. Figure 8 (a) is a graph comparing the trend of nitrogen oxide adsorption performance with existing commercially available adsorbents. Figure 8 (b) is a graph comparing the amount of nitrogen oxide adsorbed with existing commercial adsorbents. Figure 9 (a) is a graph comparing the nitrogen oxide adsorption performance of Mg / KMnO4 / Al2O3. Figure 9 (b) is a graph comparing the nitrogen oxide adsorption performance of KMnO4 / Mg-Al2O3. Figure 9 (c) is a graph comparing the nitrogen oxide adsorption performance of KMnO4 / Mg / Al2O3. Specific details for implementing the invention

[0013] FIG. 1 is a flowchart of a method for manufacturing a nitrogen oxide adsorbent using KMnO4 according to one embodiment of the present invention.

[0014] According to FIG. 1, a method for manufacturing a nitrogen oxide adsorbent using KMnO4 according to one embodiment of the present invention may include the steps of forming a composite support (S100), preparing a precursor solution (S200), impregnating the composite support with the precursor solution to form a sample (S300), drying the sample (S400), and finally drying the sample (S500).

[0015] The step of forming a composite support (S100) may involve mixing a first support and a second support to form the composite support. At this time, the nitrogen oxide adsorption performance of the formed composite support may vary depending on the particle sizes of the first and second supports used.

[0016] Figure 2(a) is a graph comparing the nitrogen oxide adsorption performance of adsorbents prepared according to different aluminum oxide particle sizes based on volume, and Figure 2(b) is a graph comparing the nitrogen oxide adsorption performance of adsorbents prepared according to different aluminum oxide particle sizes based on weight. In addition, Figure 3 is a graph comparing the adsorption rates and trends of nitrogen oxides according to Figure 2.

[0017] To obtain the graphs of Figures 2 and 3, nitrogen oxide adsorption experiments were performed using an adsorbent supported with potassium permanganate (KMnO4). Specifically, aluminum oxides with different average particle sizes were used as supports, and an adsorbent sample was prepared by supporting potassium permanganate at the same weight ratio of 8 wt% relative to the weight of the aluminum oxide supporting the aluminum oxide. At this time, all manufacturing conditions except for the particle size of the aluminum oxide were kept the same.

[0018] More specifically, nitrogen oxide adsorption experiments were conducted using a fixed-bed reactor packed with adsorbent samples. The experiment was carried out by continuously supplying a mixed gas with a nitrogen oxide concentration of 113 ppm to the reactor. Air was used as the equilibrium gas for the reaction, and the gas flow rate was maintained constant at 1,000 cc / min. The packing volume of the adsorbent was standardized to 1,507.2 mm³ to ensure that performance differences based on support particle size were not caused by variations in the amount of adsorbent. Additionally, the experiment was performed while maintaining the reactor temperature at 40 ℃, and the relative humidity of the reaction gas was adjusted to 80% to simulate actual exhaust gas conditions. During the adsorption experiment, the nitrogen oxide concentration at the reactor outlet was continuously measured to analyze the breakthrough behavior of nitrogen oxides over time.

[0019] The measured nitrogen oxide adsorption performance was calculated and compared as total nitrogen oxide adsorption capacity (L / L) based on the adsorbent packing volume and total nitrogen oxide adsorption capacity (mg / g) converted based on the adsorbent mass, respectively. Through this, the difference in nitrogen oxide adsorption performance according to aluminum oxide particle size was quantitatively evaluated.

[0020] Referring to Figure 2, the particle size of the support can be seen to have an effect on the adsorption performance of nitrogen oxides, and the difference in adsorption performance of nitrogen oxides can be observed when the adsorbent is prepared by varying the particle size of aluminum oxide (Al2O3) among the components constituting the composite support in terms of volume and weight.

[0021] Specifically, nitrogen oxide adsorption experiments were conducted by varying only the average particle size of aluminum oxide while maintaining the loading amount of potassium permanganate (KMnO4) at a constant level. As a result, it was confirmed that the total adsorption amount of nitrogen oxides varied significantly depending on the particle size of the aluminum oxide. Different adsorption performances were observed in both volume-based (L / L) and weight-based (mg / g) nitrogen oxide adsorption capacities as the particle size of the aluminum oxide changed. This is attributed to the fact that the particle size of the support influences the pore structure, specific surface area, and gas diffusion pathways, thereby altering the loading distribution of potassium permanganate and the contact efficiency with nitrogen oxides. In particular, when using aluminum oxide with a particle size within a certain range, the nitrogen oxide adsorption performance was relatively superior, indicating that optimizing the particle size of the support is a critical factor in improving adsorption performance.

[0022] Referring to Figure 3, the adsorption behavior of nitrogen oxides according to the particle size of aluminum oxide was analyzed over time, and it was confirmed that the breakthrough characteristics of nitrogen oxides differ significantly depending on the particle size. In particular, when aluminum oxide with an average particle size in the range of about 50 μm to 200 μm was used as a support, the ratio of inlet concentration to outlet concentration (C / CO) was maintained at a state close to 0 for a long time in the initial section of the experiment, indicating that nitrogen oxides were stably adsorbed, and the breakthrough onset time also tended to be relatively delayed.

[0023] Conversely, when aluminum oxide with an excessively small average particle size was used, significant fluctuations in the C / CO value occurred from the beginning, and breakthrough occurred relatively rapidly, leading to a tendency for nitrogen oxide adsorption to fail to be maintained stably. This is attributed to the fact that the use of fine particles limits effective contact between the active ingredient and nitrogen oxides due to factors such as support aggregation, reduced pore accessibility, or inhibited diffusion. Furthermore, when the average particle size is relatively small, the passage path of nitrogen oxides is formed non-uniformly during the adsorption process, which may result in unstable breakthrough behavior.

[0024] As such, the particle size of aluminum oxide directly affects not only the initial efficiency of nitrogen oxide adsorption but also the breakthrough point and adsorption stability. In particular, when the average particle size is in the range of about 50 μm to 200 μm, the breakthrough of nitrogen oxide is delayed and stable adsorption behavior is ensured. Therefore, in the method for manufacturing a nitrogen oxide adsorbent of the present invention, the aluminum oxide used as a support may preferably have an average particle size in the range of 50 μm to 200 μm.

[0025] In the experiment according to FIGS. 2 and 3, the loading amount of potassium permanganate was fixed to a specific value for convenience to evaluate the effect of aluminum oxide particle size, but this is merely a representative example to confirm the trend of adsorption performance according to changes in support particle size. The results are attributed to differences in pore structure and diffusion characteristics according to aluminum oxide particle size, and similar trends can be applied even when the loading amount of potassium permanganate changes.

[0026] Accordingly, in the method for manufacturing a nitrogen oxide adsorbent according to one embodiment of the present invention, by appropriately selecting and controlling the particle size of aluminum oxide constituting the support in the step (S100) of forming a composite support, the loading state of potassium permanganate and the nitrogen oxide adsorption behavior can be optimized, and thereby, improved nitrogen oxide adsorption performance compared to conventional adsorbents can be achieved.

[0027] In addition, the first support and the second support can be mixed using a ball mill. For example, a composite support can be formed by introducing a first support containing magnesium oxide (MgO) and a second support containing aluminum oxide (Al2O3) into a ball mill and performing mechanical mixing. In this case, the ball mill process can serve as a means to control the dispersion state and contact structure between support particles, going beyond simple physical mixing.

[0028] When operating a ball mill, zirconia balls of multiple sizes can be mixed and used together with the first support and the second support. Specifically, the zirconia balls can be classified into balls with a relatively large diameter, balls with an intermediate diameter, and balls with a small diameter and fed together. By using a mixture of zirconia balls of different sizes, impact, shear, and frictional actions applied to the support particles can occur in combination. These actions promote uniform dispersion and mixing of the support particles, thereby contributing to the formation of a more homogeneous composite support.

[0029] Zirconia balls can be used by mixing large, medium, and small balls within a specific weight ratio range, and the weight ratio of balls of each size can be set considering the energy transfer efficiency and mixing characteristics within the ball mill.

[0030] As an example of one embodiment, zirconia balls classified into diameters of 20 mm, 10 mm, and 5 mm can be mixed with a support and operated in a ball mill to form a composite support. Large balls may be used in an amount of about 3 to 10% of the total weight of the balls, medium balls in an amount of about 15 to 25%, and small balls in an amount of about 20 to 30%. By having zirconia balls of different sizes work together within this range, impact, shear, and frictional energy applied to the support particles inside the ball mill can be distributed and transmitted in stages.

[0031] Large balls primarily serve to alleviate aggregation between support particles by providing impact energy, medium balls promote mixing and shearing between supports, and small balls induce fine dispersion and homogenization, thereby contributing to the formation of a uniform mixture throughout the composite support. Accordingly, when zirconia balls are mixed and used in the weight ratio range described above, the effect of improving dispersion uniformity and process reproducibility of the composite support can be expected.

[0032] However, the weight ratio of zirconia balls by size is not limited to this, and can be appropriately selected and adjusted within the above range depending on the particle size of the support, the target dispersion state, the operating conditions of the ball mill, etc.

[0033] In this way, a composite support can be formed by feeding zirconia balls of different diameters together with a support into a ball mill and operating it, but the present invention is not limited thereto, and the size combination of zirconia balls and the weight ratio of each size can be varied depending on the physical properties of the support, the target dispersion state, and the process conditions.

[0034] In the process of forming a composite support by mixing the first support and the second support in a ball mill, the operating time and rotational speed of the ball mill can directly affect the dispersion uniformity and pore structure of the composite support, as well as the loading distribution of potassium permanganate (KMnO4) and the effective contact efficiency with nitrogen oxides.

[0035] Accordingly, in the present invention, under conditions of NOx concentration of 113 ppm (air balance), flow rate of 1,000 cc / min, temperature of 40 ℃, and relative humidity of 80%, while maintaining the adsorbent filling volume at the same level of 1507.2 mm³, zirconia balls having sizes of 20 mm, 10 mm, and 5 mm were mixed, and the nitrogen oxide adsorption performance of samples prepared by varying the ball mill operation time and rotation speed was compared.

[0036] Figure 4 (a) is a graph comparing the nitrogen oxide adsorption performance according to the control of the ball mill's operating time, and Figure 4 (b) is a graph comparing the nitrogen oxide adsorption performance according to the ball mill's rotation speed.

[0037] Referring to Figure 4, compared to a conventional commercial nitrogen oxide adsorbent (Commercial B) that does not contain magnesium oxide (MgO) as a first support and a 20% KMnO₄ / Al₂O₃ adsorbent, the adsorbent prepared by controlling the ball mill operating time and rotation speed and containing magnesium oxide (MgO) as a first support showed a significant difference in nitrogen oxide adsorption behavior.

[0038] Here, KMnO4 / Mg-Al2O3 is based on the weight ratio of aluminum oxide (Al2O3) during manufacturing, and all weight ratios shown in the chemical formula are based on Al2O3. For example, in the case of 20% KMnO4 / 8% Mg-Al2O3, it means that the adsorbent is composed of magnesium oxide (MgO) at 8% and potassium permanganate (KMnO4) at 20% by weight, based on Al2O3 used as the second support.

[0039] First, in the case of Commercial B, the ratio of inlet concentration to outlet concentration (C / CO) rose relatively rapidly from the beginning of the experiment, leading to early breakthrough; consequently, the nitrogen oxide storage capacity and long-term adsorption stability were found to be limited. This suggests that while commercial adsorbents can provide a certain level of adsorption performance under general operating conditions, their nitrogen oxide adsorption capacity may rapidly deteriorate under high humidity or long-term operating conditions.

[0040] Meanwhile, in the case of the 20% KMnO4 / Al2O3 adsorbent without magnesium oxide as the first support, compared to Commercial B, the breakthrough point of nitrogen oxides was partially delayed and the total adsorption amount tended to increase; however, the increase in C / CO after breakthrough proceeded relatively rapidly, indicating that there were still limitations in terms of the stability of adsorption performance. This is believed to be because it is difficult to sufficiently control the dispersion of active components within the support and effective contact with nitrogen oxides solely by increasing the loading amount of potassium permanganate.

[0041] In contrast, for an adsorbent prepared by forming a composite support containing magnesium oxide (MgO) as a first support and aluminum oxide (Al2O3) as a second support, and then appropriately controlling the ball mill operating time and rotation speed, the C / C0 ratio was maintained at a near-zero state for a long time during the initial experimental period, exhibiting behavior in which nitrogen oxides were stably adsorbed. Furthermore, the breakthrough onset was significantly delayed compared to Commercial B and the 20% KMnO4 / Al2O3 adsorbent, and even after breakthrough, the increase in C / C0 proceeded relatively slowly, confirming that stable adsorption performance was maintained even under long-term operating conditions.

[0042] This improvement in performance is attributed to the fact that the composite support containing magnesium oxide (MgO) provides basic surface characteristics, thereby creating an environment favorable for the capture and storage of nitrogen oxides, and at the same time, the dispersion uniformity and pore structure of the support are optimized through the control of the ball mill operation time and rotation speed, thereby stabilizing the loading state of potassium permanganate (KMnO4). In other words, unlike conventional technologies that simply increase the loading amount of active ingredients, it can be concluded that the adsorbent according to the present invention simultaneously improves nitrogen oxide adsorption performance and adsorption stability by controlling the support composition and manufacturing process together.

[0043] Accordingly, the adsorbent produced by forming a composite support containing magnesium oxide (MgO) as the first support and appropriately adjusting the ball mill operating time and rotation speed exhibits superior nitrogen oxide adsorption performance compared to existing commercial nitrogen oxide adsorbents and potassium permanganate (KMnO4) supported adsorbents that do not contain magnesium oxide (MgO), and it can be seen that these composition and manufacturing conditions are the core technical features of the present invention.

[0044] In addition, in the experiment conducted in Figure 4, the difference in adsorption performance of nitrogen oxides when the ball mill operation time or rotation time was varied is shown in Tables 1 and 2 below based on volume and mass.

[0045] Ball mill operation time NOx adsorption capacity (mmol / cc) NOx adsorption capacity (L / L) NOx adsorption capacity (mg / g) 1 hour 1.552 37.946 53.982 3 hours 1.163 28.435 43.812 5 hours 1.418 34.670 45.485

[0046] Ball mill rotation speed NOx adsorption capacity (mmol / cc) NOx adsorption capacity (L / L) NOx adsorption capacity (mg / g) 100 rpm 1.232 30.122 45.673 300 rpm 1.163 28.435 43.812 500 rpm 0.859 21.003 30.578

[0047] Referring to Tables 1 and 2, the total adsorption capacity of nitrogen oxides varies significantly depending on the ball mill operating time and rotational speed, which implies that an optimal range exists for ball mill process conditions. If the ball mill operating conditions are excessive, the nitrogen oxide adsorption performance may actually decrease. Specifically, in the method for manufacturing a nitrogen oxide adsorbent according to the present invention, the ball mill can be operated for 1 to 5 hours at a rotational speed of 100 to 500 rpm, and most preferably, breakthrough is delayed and the total adsorption amount of nitrogen oxides can increase when the operating time is 1 hour at 100 rpm. Furthermore, as shown in Tables 1 and 2, it can be seen that the adsorption performance of the nitrogen oxide adsorbent according to the present invention exhibits the same trend regardless of whether it is evaluated by volume (mmol / cc, L / L) or mass (mg / g). This implies that the improvement in adsorption performance of the present invention is not dependent on a specific evaluation unit, but is attributed to structural improvements in the composite support according to the ball mill operating conditions.

[0048] Figure 5 is a graph comparing the nitrogen oxide adsorption performance of the ball mill according to Figure 4 at different reaction temperatures.

[0049] Referring to Figure 5, the breakthrough behavior of the adsorbent according to the change in reaction temperature can be compared, and the adsorption performance and stability can be determined through the increasing pattern of the effluent concentration ratio (C / CO) over time.

[0050] When the reaction temperatures are 20 ℃, 40 ℃, and 60 ℃, the C / C0 value remains close to 0 in the initial range, exhibiting stable adsorption behavior where the breakthrough point arrives gradually. In particular, the time to reach C / C0 = 0.5 tends to be significantly delayed at 40 ℃ and 60 ℃ compared to 20 ℃, indicating that the adsorption active site is stably maintained within this temperature range. Furthermore, the slope of the adsorption curve is gentle within this temperature range, characterized by the fact that the performance degradation of the adsorbent does not occur abruptly.

[0051] On the other hand, as the reaction temperature increases to 80 ℃ and 100 ℃, the C / CO value rises sharply after the initial adsorption region, and the breakthrough point tends to occur relatively early. In particular, under the 100 ℃ condition, the slope of the adsorption curve increases sharply, confirming that the adsorbent reaches a saturation state within a relatively short period of time. This is attributed to the fact that the stability of the adsorption reaction decreases under high-temperature conditions, or that the desorption of adsorbed nitrogen oxides becomes relatively easier.

[0052] In this way, by performing the ball milling process within a specific temperature range, excessive thermal deformation of the adsorbent particles can be prevented, and the dispersibility of the active ingredient and the binding stability with the support can be simultaneously secured. Consequently, the manufactured adsorbent provides the effect of exhibiting excellent sustained adsorption performance under low and medium temperature conditions. Accordingly, in the method for manufacturing a nitrogen oxide adsorbent according to the present invention, the ball mill can be operated in a temperature range of 20 to 60 ℃.

[0053] Figure 6 (a) is a graph comparing the nitrogen oxide adsorption performance according to the presence or absence of moisture during the ball mill operation conditions, and Figure 6 (b) is a graph comparing the nitrogen oxide adsorption performance according to the presence or absence of oxygen during the ball mill operation conditions.

[0054] Figure 6(a) shows the adsorption behavior under conditions of 80% relative humidity. Under these conditions, the adsorbent maintains a C / C0 value close to zero in the initial phase and exhibits a relatively gradual increase in concentration even after the breakthrough point. This implies that the adsorption reaction proceeds stably in an environment where a certain level of moisture is present. Furthermore, while moisture can generally act as a competitive adsorption factor for active sites in the adsorption process, it was found that continuous adsorption behavior is maintained under these conditions (RH 80%) without a rapid decline in adsorption performance. These results suggest that if the adsorbent is operated under moderate humidity conditions, its adsorption performance can be exhibited more stably.

[0055] Accordingly, in the method for manufacturing a nitrogen oxide adsorbent of the present invention, it is preferable that the ball mill be operated in an environment where a certain level of humidity is maintained relative to dry conditions, and in particular, at a relative humidity level of about 80%, the effect of ensuring stability of adsorption performance can be achieved.

[0056] Figure 6(b) shows the results of comparing adsorption performance based on the presence or absence of oxygen. Under conditions where oxygen is present (With O2), the C / C0 value is maintained at a low level for a long time, and the breakthrough point tends to be relatively delayed. On the other hand, under conditions where oxygen is absent (Without O2), it can be observed that the C / C0 value increases rapidly after initial adsorption and reaches a saturation state within a relatively short period of time. This is attributed to the fact that the adsorption reaction is maintained more stably in an environment where oxygen is present, or that the re-emission of adsorbed nitrogen oxides is suppressed.

[0057] Therefore, it can be seen that the operating conditions of the ball mill in the method for manufacturing a nitrogen oxide adsorbent according to the present invention exhibit excellent sustained adsorption performance under conditions where oxygen is present, and are suitable for application in environments containing oxygen, such as actual exhaust gas or process gas.

[0058] The step of preparing a precursor solution (S200) can be prepared by dissolving potassium permanganate (KMnO4) in purified water. Specifically, as a step of preparing a precursor solution capable of impregnating a composite support, it is preferable to use purified water as a solvent to suppress reaction interference or precipitation formation caused by ionic impurities and to ensure reproducibility of loading. Potassium permanganate has the property of being soluble in water, so it can be prepared in the form of an aqueous solution even at room temperature; for example, a water solubility of about 6.4 g / 100 mL at 20 ℃ has been reported, so a precursor solution of an appropriate concentration can be easily prepared according to the required loading amount.

[0059] In addition, potassium permanganate can be dissolved in purified water to prepare a precursor solution with a concentration corresponding to the target amount of loading and the degree of impregnation, and then, in a subsequent step (S300), the precursor solution can be dropped onto a composite support to impregnate it, thereby performing loading.

[0060] The precursor solution can be used immediately after preparation, or, if necessary, after ensuring uniformity of the solution concentration through stirring. Considering that solubility increases with temperature changes, the solution temperature may also be controlled during preparation when a high concentration is required. This allows potassium permanganate to penetrate uniformly into the surface and pores of the composite support, thereby improving the reproducibility of the loading distribution and the stability of the adsorption performance when combined with subsequent repeated impregnation and drying processes.

[0061] The step of forming a sample by impregnating a composite support with a precursor solution (S300) can form a sample by impregnating the composite support formed in the step of forming a composite support (S100) with a precursor solution containing potassium permanganate (KMnO4) prepared in the step of preparing a precursor solution (S200). Specifically, impregnation can be carried out by dripping the precursor solution onto the composite support.

[0062] Specifically, a precursor solution in which potassium permanganate is dissolved is dropped onto the manufactured composite support in small amounts using a dropper or an equivalent dropping means. At this time, the precursor solution is dropped within a range that does not saturate the support so that it is naturally absorbed by the surface and pore structure of the composite support, and potassium permanganate may be used in a state dissolved in a minimum amount of purified water. The amount of precursor solution to be dropped may be supplied only to the extent that it wets the support, taking into account the volume and liquid absorption characteristics of the composite support.

[0063] In addition, by mixing or stirring the composite support simultaneously with the dropping of the precursor solution, potassium permanganate can be uniformly distributed on the surface and internal pores of the support. Subsequently, by drying the composite support on which the precursor solution has been dropped to remove moisture and repeating the process of dropping the precursor solution again, the loading amount and loading distribution of potassium permanganate within the composite support can be controlled stepwise.

[0064] Figure 7 is a graph comparing the nitrogen oxide adsorption performance according to the potassium permanganate content.

[0065] In order to test the nitrogen oxide adsorption performance according to the content of potassium permanganate (KMnO4) through Figure 7, the nitrogen oxide adsorption behavior was evaluated in the case where the adsorbent was composed of potassium permanganate alone and in the case where potassium permanganate was combined with a support at a certain content to form a composite support. The experiment was conducted under the same conditions as the experiment in Figure 4, with only the potassium permanganate content being different, and the average particle size of Al2O3 was set to 50 to 200 μm.

[0066] Referring to Figure 7, when the adsorbent was composed solely of potassium permanganate, the ratio of inlet concentration to outlet concentration (C / CO) increased rapidly from the beginning of the experiment, leading to rapid breakthrough; consequently, it can be seen that the storage capacity and adsorption stability of nitrogen oxides are limited. This is attributed to the fact that when potassium permanganate is used alone, the active component is not effectively dispersed and supported, and effective contact with nitrogen oxides is not sufficiently secured due to the absence of a pore structure.

[0067] Meanwhile, when potassium permanganate was loaded at different concentrations on the same support to form a composite support, a tendency for different nitrogen oxide adsorption behaviors was observed. Specifically, when the potassium permanganate content was low, such as 1%, the breakthrough point was partially delayed, but the improvement in adsorption performance was limited; in contrast, at a content of 8%, the breakthrough delay effect and adsorption stability showed a tendency to improve further. Furthermore, when the potassium permanganate content increased above a certain level, such as at 20%, a state where C / CO was close to zero was maintained for a long time in the initial experimental section, and the breakthrough onset point was significantly delayed, indicating a substantial improvement in nitrogen oxide storage capacity. This is attributed to the fact that potassium permanganate was effectively dispersed and immobilized by the pore structure and surface characteristics provided by the support, thereby maximizing the effective contact area between the active ingredient and nitrogen oxides.

[0068] Based on these results, in order to more clearly compare the effect of potassium permanganate content on nitrogen oxide adsorption performance, a composite support adsorbent containing 20 wt% potassium permanganate relative to the second support was evaluated for comparison with existing commercial nitrogen oxide adsorbents.

[0069] Figure 8 (a) is a graph comparing the trend of nitrogen oxide adsorption performance with existing commercial adsorbents, and Figure 8 (b) is a graph comparing the amount of nitrogen oxide adsorbed with existing commercial adsorbents.

[0070] Referring to Fig. 8, when potassium permanganate is loaded at 20% relative to the weight of the second support, the breakthrough point is significantly delayed compared to existing commercial adsorbents A and B, and the adsorption behavior over time is maintained more smoothly, exhibiting stable nitrogen oxide adsorption performance even under long-term operation conditions. In addition, as a result of comparing the total nitrogen oxide adsorption capacity, it can be seen that the 20% potassium permanganate composite support adsorbent exhibits a significantly higher adsorption capacity compared to commercial adsorbents.

[0071] As such, when the potassium permanganate content is excessively low, the improvement in adsorption performance is limited due to an absolute lack of active ingredients. Conversely, when potassium permanganate is used alone without a support, the utilization efficiency of the active ingredients decreases. On the other hand, when potassium permanganate is supported on a support at a certain content to form a composite support, it can be seen that the dispersion stability and effective contact efficiency of the active ingredients are significantly improved. Therefore, in the method for manufacturing a nitrogen oxide adsorbent according to the present invention, the nitrogen oxide adsorption performance can be effectively improved by appropriately controlling the content of potassium permanganate while combined with a support, and from the above results, it can be confirmed that the content of potassium permanganate can be optimized within a certain range.

[0072] As shown in FIGS. 7 and 8, the method for manufacturing a nitrogen oxide adsorbent according to the present invention may support potassium permanganate (KMnO4) at 1 to 20% of the weight of the second support, and preferably at 20%.

[0073] In addition, adsorption performance may vary depending on the loading order.

[0074] Figure 9 (a) is a graph comparing the nitrogen oxide adsorption performance of Mg / KMnO4 / Al2O3, (b) is KMnO4 / Mg-Al2O3, and (c) is KMnO4 / Mg / Al2O3.

[0075] Referring to Fig. 9, it can be seen that even when using the same combination of components, the nitrogen oxide adsorption performance can vary significantly depending on the order in which they are loaded.

[0076] As shown in Fig. 9(a), when KMnO₄ is loaded after Mg is loaded first (Mg / KMnO₄ / Al₂O₃), a tendency for C / CO₄ to rise rapidly or fluctuate relatively significantly in the initial adsorption range is observed, suggesting that the adsorption behavior may not be constant even with the same composition. Furthermore, as shown in Fig. 9(c), when Mg is loaded after KMnO₄ is loaded first (KMnO₄ / Mg / Al₂O₃), Mg is introduced after KMnO₄ has already settled on the surface and pores of the support, making it difficult to sufficiently control the surface characteristics of the support and the dispersion state of the active component. Consequently, the breakthrough delay effect may be limited or the adsorption efficiency may be reduced.

[0077] In contrast, as shown in Fig. 9 (b), in the sequence where a composite support (Mg-Al2O3) is formed by first mixing the Mg component and Al2O3, followed by the loading of KMnO4 (KMnO4 / Mg-Al2O3), a low C / C0 state is maintained for a relatively longer period and breakthrough is delayed, which clearly shows an improved storage capacity and adsorption stability of nitrogen oxides. This is interpreted as being due to the fact that KMnO4 is loaded while the Mg component is first uniformly reflected on the surface and pore structure of the support, thereby allowing KMnO4 to be more uniformly dispersed and immobilized within the support and increasing effective contact with nitrogen oxides.

[0078] Therefore, if the loading order is not properly controlled, the nitrogen oxide adsorption performance may vary even with the same composition, and the best nitrogen oxide adsorption performance can be achieved when manufactured in the preferred loading order according to the present invention, that is, by first forming a composite support (Mg-Al2O3) containing an Mg component and then loading KMnO4.

[0079] The step of drying the sample (S400) is a step performed to remove moisture from the sample impregnated with the precursor solution through the step of forming the sample (S300). In this step, by drying the sample immediately after impregnation, the solvent components contained in the precursor solution can be removed and potassium permanganate can be immobilized on the surface of the support and within the pores.

[0080] Specifically, drying can be performed using an oven, for example, at a temperature range of about 80°C to 120°C, more preferably at about 100°C for about 30 minutes to 1 hour. However, the drying conditions can be appropriately adjusted according to the amount of sample, the amount of impregnated precursor solution, and the liquid absorption characteristics of the support.

[0081] In addition, in the present invention, the step of forming a sample (S300) and the step of drying the sample (S400) can be alternately repeated several times until a target loading amount or a preset degree of impregnation is reached. Specifically, this repetitive impregnation and drying process can be repeated until the sample reaches a preset degree of impregnation. Here, the preset degree of impregnation may refer to a state in which the weight increase of the sample becomes negligible or no longer increases as the impregnation and drying process is repeated. For example, if there is no change based on the point in time when the weight increase rate of the sample decreases to less than 1% between the consecutive steps of forming the sample (S300) and drying the sample (S400), subsequent processes can be carried out.

[0082] Through this iterative process, the precursor components can be controlled to be uniformly loaded across the entire support, while preventing excessive concentration on the surface of the support or blockage of pores.

[0083] By repeating the process of dropping, absorbing, and drying the precursor solution in this manner, potassium permanganate can be uniformly loaded without excessively blocking the pores of the composite support, which can contribute to improving the reproducibility and stability of adsorption performance by increasing the effective contact area with nitrogen oxides.

[0084] The drying in the sample drying step (S400) corresponds to an intermediate drying step performed between each impregnation step, and after repeated impregnation is completed, a final drying step (S500) of the dried sample can be performed as a subsequent process.

[0085] The final drying step (S500) is a step performed to stabilize potassium permanganate supported within a composite support and sufficiently remove residual moisture after the sample forming step (S300) and the sample drying step (S400) have been repeated. Unlike the sample drying step (S400), the final drying step (S500) can be performed for the purpose of final moisture removal and physical stabilization of the sample after repeated impregnation is completed.

[0086] Specifically, final drying can be performed using an oven, for example, at a temperature range of about 80°C to 120°C for a predetermined period of time. Subsequently, if necessary, trace amounts of moisture remaining inside the sample may be removed by storing the sample, after oven drying is complete, in a low-humidity environment such as a desiccator to dry it further. For example, a method of stabilizing the sample by leaving it in a desiccator for several hours to tens of hours after oven drying can also be applied as one example.

[0087] This allows potassium permanganate supported during repeated impregnation processes to be more stably immobilized on the surface and within the pores of the support, thereby improving the storage stability and reproducibility of the adsorbent. Additionally, the final drying conditions can be appropriately adjusted according to the amount of sample, the amount of supported precursor, and the required adsorption characteristics.

[0088] As such, the method for manufacturing a nitrogen oxide adsorbent using KMnO4 according to one embodiment of the present invention optimizes the dispersion state according to the mixing conditions of the composite support, the dropping impregnation method of the potassium permanganate precursor, the repeated process of impregnation and drying, and the ball mill operation conditions, thereby increasing the breakthrough time of nitrogen oxides compared to conventional commercial adsorbents and maintaining stable adsorption performance even during long-term operation, while simultaneously enabling the production of a nitrogen oxide adsorbent capable of mass production through process simplification and reproducibility.

[0089] Although embodiments of the present invention have been described above, the spirit of the present invention is not limited to the embodiments presented in this specification. Those skilled in the art who understand the spirit of the present invention may easily propose other embodiments within the scope of the same spirit by adding, changing, deleting, or adding components, and such embodiments shall also be considered to fall within the scope of the spirit of the present invention.

Claims

Claim 1 A method for manufacturing an adsorbent for adsorbing nitrogen oxides comprises: (a) forming a composite support (Mg-Al2O3) by mixing a first support containing magnesium oxide (MgO) and a second support containing aluminum oxide (Al2O3) having an average particle size of 50 μm to 200 μm using a ball mill; (b) preparing a precursor solution by dissolving potassium permanganate (KMnO4) in purified water; (c) forming a sample by impregnating the composite support (Mg-Al2O3) with the precursor solution containing KMnO4 by dropping it onto it; and (d) drying the sample. A method for manufacturing a nitrogen oxide adsorbent using KMnO4, comprising the step of (e) finally drying the dried sample, wherein steps (c) and (d) are repeated until the sample reaches a preset degree of impregnation, and wherein the ball mill uses a mixture of zirconia balls having sizes of 20 mm, 10 mm, and 5 mm, and is operated at a rotational speed of 100 to 500 rpm for 1 to 5 hours at a temperature range of 20 to 60 ℃. Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 delete

Citation Information

Patent Citations

  • METHOD FOR IMPROVING NOx REMOVAL EFFICIENCY FROM FLUE GAS AND REDUCING CONSUMPTION OF AMMONIA AND EMISSION OF NITROGEN DIOXIDE USING MODIFIED NATURAL MANGANESE ORES

    KR1020020051885A

  • METHOD FOR PREPARING DeNOx CATALYST USING A SUPPORT OF NANO DISPERSED TITANIUM DIOXIDE SOL

    KR1020250069742A

  • Solid particulate carrier, wherein permanganate is adsorbed

    JP1994324049A

  • Composition Based on Manganese and Use for TrappingNOx for Treating Exhaust Gases

    KR1020010032453A